Increased dietary methionine, lysine and histidine supply modulated the heat stress-induced metabolic remodeling of dairy cows - Jorge-Smeding, Ezequiel; Ruiz-González, Alexis; Leung, Yue Hei; Trujillo, Ana Inés; Astessiano, Ana Laura; Ouellet, Daniel R.; Lapierre, Hélène; Rico, Daniel E.; Kenéz, Ákos (Frontiers in Animal Science, 2024)
Increasing dietary Met, Lys and His supply without increasing dietary protein content were shown to partially alleviate the productive and physiological effects of heat stress. Nevertheless, the metabolic pathways involved are yet to be identified. Twelve lactating Holstein cows (primiparous, n = 6; multiparous, n = 6; 42.2 ± 10.6 kg/d milk yield; 83 ± 28 days in milk) were enrolled in two 3×3 replicated Latin squares consisting of 14-day treatment periods: heat stress (HS; max. Temperature Humidity Index (THI) 84, 16.8% crude protein (CP), 1,740 g/d metabolizable protein (MP), 108 Lys, 33 Met, and 37 His (g/d)), pair feeding in thermo-neutrality (TN; max. THI 64, same diet as HS), and HS with increased Lys, Met and His supply (HS+AA; max. THI 84; 17.0 % CP, 1,755 g/d MP, 179 Lys, 58 Met, and 45 His (g/d)). Blood plasma and milk were sampled on day 14 for metabolomics profiling. Several amino acids (AA) and derivatives differed between the treatments. Plasma and milk Met, Val, Trp and α-amino adipic acid concentrations were highest in HS+AA (false discovery rate-P (FDR) < 0.05). Moreover, only plasma Lys and milk His were highest in HS+AA (FDR < 0.05). Some phosphatidylcholines (PC) and diglycerides had lower concentrations in HS than TN (FDR < 0.05), while HS+AA had similar concentrations as TN. The pathway enrichment analysis revealed that the AA-related pathways were more significantly affected in multiparous than in primiparous cows. Our results suggest that increased supply of Met stimulated PC synthesis in HS+AA to similar concentrations as in TN. Increased Lys supply likely elevated the oxidation rate of Lys and downregulated the catabolism of other essential AA (EAA) such as Val and Trp, stimulating milk protein synthesis. No clear associations were found related to His availability. In conclusion, partial amelioration of productive and physiological effects of heat stress associated with increased dietary Met and Lys supply were likely explained by stimulated PC synthesis and increased plasma and milk concentrations of other EEA.